Diversidade de algas verdes em crostas biológicas de solo do cerrado - Tralli, Marcella Palhiari [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Green algae are a higly diversified group and their representatives can be found in many types of habitats. On soils, green algae, in association with other organisms, may form biological crusts, a community considered relevant in some ecosystems (especially in arid and semi-arid environments). They are pioneer in soil systems, helping to reduce erosion by stabilizing and improving the physical and chemical properties of soils and influencing the germination of different plants. This study aims to the taxonomic survey of green algae assemblages found in savannah areas in the states of São Paulo and Minas Gerais. In addition, the comparison of taxonomic compositions of the assemblages from different localities and the molecular characterization of the most frequent species are complementary objetives. The sampled material was directly examined under light microscope and also cultivated on artificial growth media. The results obtained are based on the analyzes of 40 samples collected in April 2013. The taxonomic survey resulted in the finding of 17 morphotypes pertaining to Trebouxiophyceae, Chlorophyceae, Ulvophyceae, Klebsormidiophyceae and Conjugatophyceae. Two out 17 identifications were possible only to the generic level (Chlorococcum sp. and Klebsormidium sp.) due to the absence of reproductive stages. One population was not identified due to the inconsistence of the observed characteristics to identify. Four occurrences are new records for the country. The two study areas showed distinct floristic composition, with only six occurrences common to both parks. The highest species richness was recorded in the Serra da Canastra National Park, with 14 morphotypes, while in the State Park Furnas do Bom Jesus were recorded only seven. Soil nutrients, moisture, temperature and pH have shown that the occurrence of a species cannot be addressed to a single environmental variable, but possibly two or more...

As algas verdes representam um grupo bastante diversificado e seus representantes podem ser encontrados em muitos tipos de habitats. Nos solos, as algas verdes, em associação com outros organismos, podem originar as crostas biológicas, uma comunidade considerada relevante nos ecossistemas (especialmente nos áridos e semiáridos). São colonizadores, auxiliando na redução da erosão, estabilizando e melhorando as propriedades físicas e químicas dos solos e também influenciando a germinação de diferentes plantas. O estudo proposto visa o levantamento taxonômico das assembleias de algas verdes encontradas em áreas de cerrado nos estados de São Paulo e Minas Gerais (Parque Estadual Furnas do Bom Jesus e Parque Nacional Serra da Canastra, respectivamente). Também pretende-se realizar a comparação da biota encontrada nos ambientes estudados e a caracterização molecular das espécies mais frequentes. O material coletado foi submetido a exame direto sob microscópio de luz e também a cultivo em meio artificial. Os resultados obtidos baseiam-se nas análises de 40 amostras coletadas em abril de 2013. O levantamento taxonômico resultou em 17 morfotipos, incluídos nas classes Trebouxiophyceae, Chlorophyceae, Ulvophyceae, Klebsormidiophyceae e Conjugatophyceae. Duas identificações foram possíveis apenas até o nível genérico (Chlorococcum sp. e Klebsormidium sp.) devido à ausência dos estágios reprodutivos e uma população não foi identificada devido à inconsistência no conjunto das características observadas. Quatro ocorrências são novos registros para o país. As duas áreas de estudo apresentaram composição florística distinta, havendo apenas seis ocorrências comuns aos dois parques. A maior riqueza específica foi registrada no Parque Nacional da Serra da Canastra, com 14 morfotipos, enquanto no Parque Estadual das Furnas do Bom Jesus foram registradas apenas sete...
Keywords: Biologia molecular; Morfologia; Alga; Alga verde; Biodiversidade; Taxonomia vegetal